Validity and reliability of the Indonesian version of the Douleur Neuropathique 4 for neuropathic pain - Sofyan, Henry Riyanto; Hartono, Chandra; Savitri, Irma; Alvonsius, Raymond Aris Nimrod; Hakim, Manfaluthy; Aninditha, Tiara (Faculty of Medicine Universitas Indonesia, 2025)
BACKGROUND The Douleur Neuropathique 4 (DN4) is a widely used questionnaire for assessing neuropathic pain, demonstrating good sensitivity and specificity across various languages. Originally developed in France, cultural and linguistic differences necessitate its translation, validation, and reliability testing before use in Indonesia. This study aimed to translate, culturally adapt, and evaluate the validity and reliability of the Indonesian version of the DN4 questionnaire (DN4-Ina) for use in clinical and research settings. METHODS Translation and cross-cultural adaptation were conducted following World Health Organization guidelines in Indonesian. A cross-sectional study was conducted in the Neurology Clinic, Cipto Mangunkusumo Hospital, to assess the validity and reliability of the DN4-Ina. The study subjects were selected through consecutive sampling of adult patients with chronic pain visiting the clinic from June to December 2023. Validity and reliability were assessed using SPSS software version 25. Validity testing utilized adjusted item-total correlation analysis, while reliability testing was evaluated using the test-retest method, intraclass correlation coefficient (ICC), and Cronbach’s alpha for internal consistency. RESULTS Of 40 participants, 65% were female, with a mean age of 51.85 (13–92) years, moderate pain intensity (mean numeric rating scale of 4.25 [2.99]), and pain duration of 7.95 (4.41) months. All DN4-Ina questions showed a correlation coefficient (r) greater than the table’s value (0.312). The reliability test showed an ICC of 0.99 and a Cronbach’s alpha of 0.746. CONCLUSIONS The DN4-Ina score is a valid and reliable questionnaire for assessing neuropathic pain in the Indonesian population.